Usability Testing pada aplikasi Zoom dengan menggunakan metode Cognitive Walkthrough - Kartika Gianina Tileng (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The Covid-19 pandemic that occurred in various parts of the world resulted in a reduction in social interactions and various activities being shifted to an online basis. One of the significant impacts that occurs is lectures that are held online. To support this online lecture, there are various technological tools that are used to assist the online process, one of which is the teleconference application. In changing the offline method to online, there are many adaptations of activities that must be carried out by lecturers and students or other students in carrying out lecture activities in higher education. Therefore, this study aims to see how the technology adaptation process in online learning sees the increasing number of online-based learning activities, to then design an application that is deemed appropriate. This research was conducted using the Cognitive Walkthrough method, using 5 respondents who were assigned according to work desks and screen recording, so it was found that the use of Zoom for 4 main features could be done well, difficulties only occurred in the second scenario.